Python Battery Mathematical Modelling (PyBaMM). (8th June 2021) - Sulzer, Valentin; Marquis, Scott G.; Timms, Robert; Robinson, Martin; Chapman, S. Jon
As the UK battery modelling community grows, there is a clear need for software that uses modern software engineering techniques to facilitate cross-institutional collaboration and democratise research progress. The Python package PyBaMM aims to provide a flexible platform for implementation and comparison of new models and numerical methods. This is achieved by implementing models as expression trees and processing them in a modular fashion through a pipeline. Comprehensive testing provides robustness to changes and hence eases the implementation of model extensions. PyBaMM is open source and available on GitHub. For more information visit www.pybamm.org .